Highly dispersive optical glass, glass preform, optical element and device
Patent Information
- Application Number
- CN202611233021.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-30
AI Technical Summary
[0016]本申请的有益效果是:通过合理的组分设计,本申请获得的高色散光学玻璃具有较低的密度以及较低的热膨胀系数。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to the field of glass technology, and in particular to high dispersion optical glass, as well as glass preforms, optical elements and devices made therefrom. Background Technology
[0002] In recent years, optical devices have rapidly developed in terms of digitization and high precision, placing higher demands on the lightweighting of optical components used in various optical devices such as digital cameras, camcorders, projectors, and projection televisions. Lenses formed from high-dispersion optical glass, combined with lenses formed from low-dispersion optical glass to create composite lenses, can correct chromatic aberration and achieve compactness of the optical system, thereby achieving the goal of lightweighting optical devices. Furthermore, using optical glass with lower density in the optical system also contributes to lightweighting. Optical components installed in automotive optical devices, as well as in heat-generating optical devices such as projectors, copiers, and laser printers, are used in environments with large temperature variations. If the coefficient of thermal expansion of the optical glass is too high, thermal expansion of the optical component will occur due to changes in ambient temperature. Because the coefficient of thermal expansion of the optical component differs from that of its mounting fixture, stress is generated within the optical component, leading to birefringence and changes in imaging characteristics. Therefore, it is desirable for optical glass to have a low coefficient of thermal expansion. Patent document CN119930146A discloses a high-dispersion optical glass with a refractive index of 1.76–1.83 and an Abbe number of 21–27, which has a high density and a high coefficient of thermal expansion (100 × 10⁻⁶). -7 (Above / K), its performance still has room for further improvement and optimization. Summary of the Invention
[0003] The technical problem to be solved by this application is to provide a high-dispersion optical glass with low density and low coefficient of thermal expansion, as well as glass preforms, optical elements and devices made therefrom.
[0004] The technical solution adopted by this application to solve the technical problem is:
[0005] The high-dispersion optical glass contains, by weight percentage: P2O5: 16%–29%; Nb2O5: 41%–53%; SiO2: greater than or equal to 1% but less than 10%; B2O3: 3%–15%; K2O: 8.5%–20%; Al2O3: greater than 0% but less than or equal to 8%, wherein the ratio of Nb2O5 / (SiO2+Al2O3) is 3.00–10.00.
[0006] In some embodiments, the high-dispersion optical glass, expressed as a weight percentage, further contains: Na₂O: 0–5%; and / or Li₂O: 0–5%; and / or ZrO₂: 0–5%; and / or WO₃: 0–5%; and / or TiO₂: 0–4%; and / or ZnO: 0–5%; and / or Ln₂O₃: 0–5%; and / or Bi₂O₃: 0–3%; and / or RO: 0–5%; and / or clarifying agent: 0–1%, wherein the RO is selected from one or more of MgO, CaO, SrO, and BaO, the Ln₂O₃ is selected from one or more of La₂O₃, Gd₂O₃, Y₂O₃, and Yb₂O₃, and the clarifying agent is selected from one or more of Sb₂O₃, SnO₂, and CeO₂.
[0007] High-dispersion optical glass contains P2O5, Nb2O5, SiO2, B2O3, K2O, and Al2O3 as essential components, expressed as weight percentages. The ratio of Nb2O5 / (SiO2+Al2O3) is 3.00–10.00. The high-dispersion optical glass has an Abbe number of 22.0–28.5 and a density of 3.40 g / cm³. 3 The coefficient of thermal expansion α is as follows. 100℃ / 300℃ 95×10 -7 / K or below.
[0008] In some embodiments, the high-dispersion optical glass contains, by weight percentage: P2O5: 16%–29%; and / or Nb2O5: 41%–53%; and / or SiO2: greater than or equal to 1% but less than 10%; and / or B2O3: 3%–15%; and / or K2O: 8.5%–20%; and / or Al2O3: greater than 0% but less than or equal to 8%; and / or Na2O: 0–5%; and / or Li2O: 0–5%; and / or ZrO2: 0–5%; and / or Or WO3: 0-5%; and / or TiO2: 0-4%; and / or ZnO: 0-5%; and / or Ln2O3: 0-5%; and / or Bi2O3: 0-3%; and / or RO: 0-5%; and / or clarifying agent: 0-1%, wherein the RO is selected from one or more of MgO, CaO, SrO, and BaO, the Ln2O3 is selected from one or more of La2O3, Gd2O3, Y2O3, and Yb2O3, and the clarifying agent is selected from one or more of Sb2O3, SnO2, and CeO2.
[0009] In some embodiments, the high-dispersion optical glass has a composition expressed as a weight percentage, wherein: Nb2O5 / (SiO2+Al2O3) is 3.50–9.00, optionally Nb2O5 / (SiO2+Al2O3) is 4.00–8.50, optionally Nb2O5 / (SiO2+Al2O3) is 5.00–7.50; and / or (K2O-Na2O-TiO2-RO-WO3) / B2O3 is 0.50–5.00, optionally (K2O-Na2O-TiO2-RO-WO3) / B2O3 is 0.50–5.00, optionally (K2O-Na2O-TiO2-RO-WO3) / B2O3 is 0.50–5.00. The ratio of (K2O-Na2O-TiO2-RO-WO3) / B2O3 is 0.80–3.00, and optionally (K2O-Na2O-TiO2-RO-WO3) / B2O3 is 1.00–2.50, further optionally (K2O-Na2O-TiO2-RO-WO3) / B2O3 is 1.10–2.00; and / or (Li2O+Na2O+TiO2+WO3+Bi2O3+ZnO) / SiO2 is below 2.00, optionally (Li2O-Na2O-TiO2-RO-WO3) / B2O3 is 1.10–2.00; The ratio of (Li₂O + Na₂O + TiO₂ + WO₃ + Bi₂O₃ + ZnO) / SiO₂ is less than 1.50, and can be further selected as (Li₂O + Na₂O + TiO₂ + WO₃ + Bi₂O₃ + ZnO) / SiO₂ less than 1.00; and / or (Li₂O + Na₂O + TiO₂ + WO₃ + Bi₂O₃ + ZnO) / SiO₂ less than 0.50; and / or (Na₂O + TiO₂ + WO₃ + Bi₂O₃ + ZnO + RO) / Al₂O₃ is less than 1.50. The content of (Na2O+TiO2+WO3+Bi2O3+ZnO+RO) / Al2O3 can be 1.00 or less, (Na2O+TiO2+WO3+Bi2O3+ZnO+RO) / Al2O3 can be 0.50 or less, and (Na2O+TiO2+WO3+Bi2O3+ZnO+RO) / Al2O3 can be 0.30 or less, wherein RO is selected from one or more of MgO, CaO, SrO, and BaO.
[0010] In some embodiments, the components of the high-dispersion optical glass are expressed as weight percentages, wherein: Al2O3 / SiO2 is 0.10–3.00, optionally Al2O3 / SiO2 is 0.20–2.00, optionally Al2O3 / SiO2 is 0.30–1.50, and further optionally Al2O3 / SiO2 is 0.40–0.80; and / or (B2O3+K2O) / P2O5 is 0.80–2.00, optionally (B2O3+K2O) / P2O5 is 0.90–1.70, optionally (B2O3+K2O) / P2O5 is 1.00–1.40; and / or K2O / ( The concentration of P2O5+TiO2 is 0.35-1.10, and K2O / (P2O5+TiO2) can be 0.40-0.95, or K2O / (P2O5+TiO2) can be 0.50-0.80; and / or (P2O5+TiO2+RO+Na2O) / Nb2O5 is 0.30-0.90, or (P2O5+TiO2+RO+Na2O) / Nb2O5 can be 0.35-0.75, or (P2O5+TiO2+RO+Na2O) / Nb2O5 can be 0.35-0.60, wherein RO is selected from one or more of MgO, CaO, SrO, and BaO.
[0011] In some embodiments, the high-dispersion optical glass comprises, by weight percentage,: P2O5: 18%–26%, optionally P2O5: greater than 20% but less than or equal to 24%; and / or Nb2O5: 43%–51%, optionally Nb2O5: 45.5%–50%; and / or SiO2: 2%–9%, optionally SiO2: 3%–8%; and / or B2O3: 5%–13%, optionally B2O3: 7%–11%; and / or K₂O: 10.5%–18%, optional; K₂O: 12%–16%; and / or Al₂O₃: 0.5%–6%, optional; Al₂O₃: 1%–5%; and / or Na₂O: 0–3%, optional; Na₂O: 0–1%, optional (Na₂O not included); and / or Li₂O: 0–3%, optional; Li₂O: 0–1%, optional (Li₂O not included); and / or ZrO₂: 0–3%, optional; ZrO₂: 0–1%, optional (ZrO₂ not included). ; and / or WO3: 0-3%, optional; WO3: 0-1%, optional (excluding WO3); and / or TiO2: 0-2%, optional; TiO2: 0-1%, optional (excluding TiO2); and / or ZnO: 0-3%, optional; ZnO: 0-1%, optional (excluding ZnO); and / or Ln2O3: 0-3%, optional; Ln2O3: 0-1%, optional (excluding Ln2O3); and / or Bi2O3: 0-2%, optional; Bi2O3: 0-1% %, optionally without Bi2O3; and / or RO: 0-3%, optionally RO: 0-1%, optionally without RO; and / or clarifying agent: 0-0.5%, optionally clarifying agent: 0-0.2%, wherein the RO is selected from one or more of MgO, CaO, SrO, BaO, Ln2O3 is selected from one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and the clarifying agent is selected from one or more of Sb2O3, SnO2, CeO2.
[0012] In some embodiments, the high-dispersion optical glass has a refractive index of 1.725–1.780, optionally 1.730–1.770, optionally 1.735–1.760; and / or an Abbe number of 22.0–28.5, optionally 23.0–28.0, optionally 24.0–27.0; and / or a coefficient of thermal expansion α. 100℃ / 300℃ 95×10 -7 For values below / K, 90×10 can be selected. -7 For values below / K, 85×10 can be selected. -7 Below / K, a further option is 80×10 -7 / K or below; and / or density of 3.40 g / cm³ 3 The following can be selected as 3.30g / cm 3 The following can be selected as 3.20 g / cm³.3 The following; and / or Young's modulus is 6800×10 7 For pressures above 10 Pa, 7000×10 Pa can be selected. 7 For pressures above 10 Pa, 7500×10 Pa can be selected. 7 Pa or higher; and / or water resistance stability of Class 2 or higher, Class 1 optional; and / or acid resistance stability of Class 2 or higher, Class 1 optional; and / or transition temperature of 580℃~650℃, 590℃~640℃ optional, 600℃~620℃ optional; and / or crystallization upper limit temperature of 1070℃ or lower, 1050℃ or lower optional, 1020℃ optional; and / or Knoop hardness of 400×10⁻⁶. 7 For pressures above 410 × 10 Pa, 410 × 10 Pa can be selected. 7 For Pa above, 420×10 can be selected. 7 Pa or above; and / or chromaticity λ 80 The wavelength is below 440 nm, optionally below 430 nm or 425 nm; and / or the viscosity at 1000℃ is 3.0 dPaS to 50.0 dPaS, optionally 5.0 dPaS to 30.0 dPaS or 8.0 dPaS to 20.0 dPaS.
[0013] The glass preform is made of the aforementioned high-dispersion optical glass.
[0014] The optical element is made of the aforementioned high-dispersion optical glass or of the aforementioned glass preform.
[0015] The device contains the aforementioned high-dispersion optical glass and / or contains the aforementioned optical elements.
[0016] The beneficial effects of this application are: through reasonable component design, the high dispersion optical glass obtained by this application has a lower density and a lower coefficient of thermal expansion. Detailed Implementation
[0017] The embodiments of the high-dispersion optical glass of this application will now be described in detail. However, this application is not limited to the embodiments described below, and appropriate modifications can be made to implement it within the scope of the purpose of this application. In addition, regarding the repeated descriptions, although there are appropriate omissions, this will not limit the main idea of the application. In the following text, the high-dispersion optical glass of this application may be simply referred to as optical glass or glass.
[0018] High-dispersion optical glass
[0019] The composition range of each component in the high-dispersion optical glass of this application is described below. In this application, unless otherwise specified, the content of each component, the total content, and the total content are all expressed as weight percentages (wt%), that is, the weight percentage of the content of each component, the total content, and the total content relative to the total amount of glass material converted into oxide composition. Here, "converted into oxide composition" refers to the total amount of oxides used as raw materials for the optical glass of this application, where the oxides, complex salts, and hydroxides decompose and transform into oxides upon melting, and the total amount of such oxides is taken as 100%.
[0020] Unless otherwise specified in the specific circumstances, the numerical ranges listed in this application include upper and lower limits, and "above" and "below" include endpoint values and all integers and fractions included in the range, but are not limited to the specific values listed when the range is defined. The term "and / or" as used herein is inclusive; for example, "A and / or B" means only A, or only B, or both A and B.
[0021] <Essential and Optional Components>
[0022] P2O5 is a network-forming component of the glass in this application, which lowers the melting temperature of the glass and optimizes light transmittance. If the P2O5 content is too low, the glass's resistance to crystallization deteriorates, and streaks easily appear. If the P2O5 content is too high, it leads to high high-temperature viscosity, poor melting performance, and difficulty in achieving the designed refractive index. Therefore, the P2O5 content in this application is 16%–29%, optionally 18%–26%, and optionally greater than 20% but less than or equal to 24%. In some embodiments, the P2O5 content can be 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0023] Nb₂O₅ is a high-refractive-index, high-dispersion component that can improve the dispersion and chemical stability of glass, and is beneficial for achieving a lower coefficient of thermal expansion. However, if the Nb₂O₅ content is too high, the glass's resistance to crystallization decreases, its density increases, and its light transmittance deteriorates. Therefore, in this application, the Nb₂O₅ content is 41%–53%, optionally 43%–51%, or optionally 45.5%–50%. In some embodiments, the Nb₂O₅ content can be 41%, 41.5%, 42%, 42.5%, 43%, 43.5%, 44%, 44.5%, 45%, 45.5%, 46%, 46.5%, 47%, 47.5%, 48%, 48.5%, 49%, 49.5%, 50%, 50.5%, 51%, 51.5%, 52%, 52.5%, 53%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0024] SiO2 can increase the viscosity of molten glass, improve its resistance to devitrification and chemical stability, and help reduce its coefficient of thermal expansion. However, if the SiO2 content is too high, the difficulty of melting the glass increases, and the transition temperature rises. Therefore, in this application, the SiO2 content is greater than or equal to 1% but less than 10%, optionally 2% to 9%, or optionally 3% to 8%. In some embodiments, the SiO2 content can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, less than 10%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0025] B2O3 can improve the melt flow properties and resistance to crystallization of glass. However, if the B2O3 content is too high, the high-temperature viscosity of the glass will be too low, and the glass will easily develop streaks. Therefore, in this application, the B2O3 content is 3% to 15%, optionally 5% to 13%, or optionally 7% to 11%. In some embodiments, the B2O3 content can be 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0026] Al2O3 can reduce the coefficient of thermal expansion of glass, improve its resistance to crystallization and Young's modulus. However, if the Al2O3 content is too high, it will lead to an excessively high glass transition temperature, and the high-temperature viscosity of the glass will be high, making it difficult to eliminate bubbles. Therefore, in this application, the Al2O3 content is greater than 0% but less than or equal to 8%, optionally 0.5% to 6%, optionally 1% to 5%. In some embodiments, the Al2O3 content can be greater than 0%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0027] In some embodiments, controlling the ratio of Al2O3 content to SiO2 content (Al2O3 / SiO2) within the range of 0.10 to 3.00 can improve the Young's modulus of the glass while preventing a decrease in its acid resistance. Therefore, an Al2O3 / SiO2 ratio of 0.10 to 3.00 is optional, an Al2O3 / SiO2 ratio of 0.20 to 2.00 is optional, a further optional Al2O3 / SiO2 ratio of 0.30 to 1.50 is optional, and an even further optional Al2O3 / SiO2 ratio of 0.40 to 0.80 is optional. In some implementations, the Al2O3 / SiO2 value can be 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, or 0.7. 5, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, 1.35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, 2.03, 2.05, 2.07, 2.10, 2.13, 2.15, 2.17, 2.20, 2.23, 2.25, 2.27, 2.30, 2. 33, 2.35, 2.37, 2.40, 2.43, 2.45, 2.47, 2.50, 2.53, 2.55, 2.57, 2.60, 2.63, 2.65, 2.67, 2.70, 2.73, 2.75, 2.77, 2.80, 2.83, 2.85, 2.87, 2.90, 2.93, 2.95, 2.97, 3.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0028] In some embodiments, by controlling the ratio of Nb2O5 content to the total content of SiO2 and Al2O3 (SiO2+Al2O3), Nb2O5 / (SiO2+Al2O3), within the range of 3.00 to 10.00, the coefficient of thermal expansion of the glass can be reduced while preventing an increase in glass density. Therefore, Nb2O5 / (SiO2+Al2O3) can be optionally 3.00 to 10.00, or 3.50 to 9.00, further optionally 4.00 to 8.50, and even more preferably 5.00 to 7.50.In some embodiments, the value of Nb2O5 / (SiO2+Al2O3) can be 3.00, 3.05, 3.10, 3.15, 3.20, 3.25, 3.30, 3.35, 3.40, 3.45, 3.50, 3.55, 3.60, 3.65, 3.70, 3.75, 3.80, 3.85, 3.90, 3.95, 4.00, 4.05, 4.10, 4.15, 4.20, 4.25, 4.30, 4.35, 4.40, 4.45, 4.50, or 4. 55, 4.60, 4.65, 4.70, 4.75, 4.80, 4.85, 4.90, 4.95, 5.00, 5.05, 5.10, 5.15, 5.20, 5.25, 5.30, 5.35, 5.40, 5.45, 5.50, 5.55, 5.60, 5.65, 5.70, 5.75, 5.80, 5.85, 5.90, 5.95, 6.00, 6.05, 6.10, 6.15, 6.20, 6.25, 6.30, 6.35, 6.40, 6 .45, 6.50, 6.55, 6.60, 6.65, 6.70, 6.75, 6.80, 6.85, 6.90, 6.95, 7.00, 7.05, 7.10, 7.15, 7.20, 7.25, 7.30, 7.35, 7.40, 7.45, 7.50, 7.55, 7.60, 7.65, 7.70, 7.75, 7.80, 7.85, 7.90, 7.95, 8.00, 8.05, 8.10, 8.15, 8.20, 8.25, 8.30 Values of 8.35, 8.40, 8.45, 8.50, 8.55, 8.60, 8.65, 8.70, 8.75, 8.80, 8.85, 8.90, 8.95, 9.00, 9.05, 9.10, 9.15, 9.20, 9.25, 9.30, 9.35, 9.40, 9.45, 9.50, 9.55, 9.60, 9.65, 9.70, 9.75, 9.80, 9.85, 9.90, 9.95, 10.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0029] K₂O acts as a flux and reduces the refractive index, and it can also lower the high-temperature viscosity of glass, which is beneficial for removing bubbles. However, excessive K₂O content can lead to an increase in the Abbe number of the glass and a decrease in chemical stability. Therefore, the K₂O content in this application is 8.5%–20%, optionally 10.5%–18%, or optionally 12%–16%. In some embodiments, the K₂O content can be 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0030] In some embodiments, by controlling the ratio (B2O3+K2O) / P2O5 between the total content of B2O3 and K2O (B2O3+K2O) and the content of P2O5 to be within the range of 0.80 to 2.00, it is beneficial for the glass to have a suitable high-temperature viscosity while achieving the desired transition temperature. Therefore, it is optional that (B2O3+K2O) / P2O5 is 0.80 to 2.00, optional that (B2O3+K2O) / P2O5 is 0.90 to 1.70, and further optional that (B2O3+K2O) / P2O5 is 1.00 to 1.40. In some implementations, the value of (B2O3+K2O) / P2O5 can be 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, 1.35, or 1. 37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0031] Na₂O can improve the formability of glass and lower its transition temperature. However, if its content is too high, it is detrimental to the coefficient of thermal expansion of the glass and will result in an excessively low transition temperature, which is unfavorable for the glass's application in high-temperature environments. Therefore, the Na₂O content is 0-5%, optionally 0-3%, or optionally 0-1%. In some embodiments, it is further optional that Na₂O is not present. In some embodiments, the Na₂O content can be 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.
[0032] Li₂O can lower the glass transition temperature; however, if its content is too high, the glass's resistance to crystallization decreases, and its weather resistance deteriorates. Therefore, the Li₂O content is 0–5%, optionally 0–3%, or optionally 0–1%. In some embodiments, it is further optional that Li₂O is not present. In some embodiments, the Li₂O content can be 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0033] ZrO2 can improve the devitrification resistance of glass, enhance its chemical stability and mechanical properties. However, if its content is too high, the melting difficulty of the glass increases, leading to inclusions within the glass and a decrease in light transmittance, while also reducing the glass's resistance to crystallization. Therefore, in this application, the ZrO2 content is 0-5%, optionally 0-3%, or optionally 0-1%. In some embodiments, it is further optional that ZrO2 is not present. In some embodiments, the ZrO2 content can be 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0034] WO3 can adjust the optical constants of glass, lower the transition temperature, and improve the glass's resistance to crystallization. However, if its content is too high, the light transmittance of the glass will decrease. Therefore, in this application, the WO3 content is 0-5%, optionally 0-3%, or optionally 0-1%. In some embodiments, it is further optional that WO3 is not present. In some embodiments, the WO3 content can be 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0035] TiO2 can improve the refractive index and dispersion of glass, but if its content is too high, the light transmittance and anti-crystallization properties of the glass will decrease. Therefore, the TiO2 content in this application is 0-4%, optionally 0-2%, optionally 0-1%. In some embodiments, it is further optional that TiO2 is not present. In some embodiments, the TiO2 content can be 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0036] In some embodiments, controlling the ratio of K2O content to the total content of P2O5 and TiO2 (P2O5+TiO2), K2O / (P2O5+TiO2), within the range of 0.35 to 1.10 can improve the hardness of the glass and optimize its light transmittance. Therefore, K2O / (P2O5+TiO2) can be selected as 0.35 to 1.10, K2O / (P2O5+TiO2) can be selected as 0.40 to 0.95, and further selected as 0.50 to 0.80. In some implementations, the value of K2O / (P2O5+TiO2) can be 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, etc., as well as all ranges and subranges between the above values. It should be understood that, in implementations, any of the above ranges can be combined with any other range.
[0037] ZnO can lower the glass transition temperature, improve the chemical stability of the glass, and reduce the high-temperature viscosity of the glass. However, if the ZnO content is too high, the glass's resistance to crystallization will deteriorate, and the glass may easily become devitrified due to its low viscosity. Therefore, the ZnO content in this application is 0-5%, optionally 0-3%, or optionally 0-1%. In some embodiments, it is further optional that the glass does not contain ZnO. In some embodiments, the ZnO content can be 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.
[0038] Ln2O3 (selected from one or more of La2O3, Gd2O3, Y2O3, and Yb2O3) is a component that improves the refractive index and chemical stability of glass. By controlling the Ln2O3 content to below 5%, the devitrification resistance of the glass can be prevented from decreasing. Therefore, in this application, the Ln2O3 content is 0-5%, optionally 0-3%, or optionally 0-1%. In some embodiments, it is further optional that Ln2O3 is not present. In some embodiments, the content of Ln2O3 can be 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0039] Bi₂O₃ can adjust the optical constants of glass and optimize its mechanical properties, but if its content is too high, the chemical stability and anti-crystallization properties of the glass will decrease. Therefore, the content of Bi₂O₃ in this application is 0-3%, optionally 0-2%, optionally 0-1%. In some embodiments, it is further optional that Bi₂O₃ is not present. In some embodiments, the content of Bi₂O₃ can be 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0040] In some embodiments, the ratio between the total content of Li2O, Na2O, TiO2, WO3, Bi2O3, and ZnO (Li2O+Na2O+TiO2+WO3+Bi2O3+ZnO) and the content of SiO2 (Li2O+Na2O+TiO2+WO3+Bi2O3+ZnO) / SiO2 is controlled below 2.00, which can reduce the coefficient of thermal expansion of the glass while preventing the glass from deteriorating in water resistance. Therefore, it is possible to select (Li2O+Na2O+TiO2+WO3+Bi2O3+ZnO) / SiO2 as 2.00 or less, (Li2O+Na2O+TiO2+WO3+Bi2O3+ZnO) / SiO2 as 1.50 or less, further select (Li2O+Na2O+TiO2+WO3+Bi2O3+ZnO) / SiO2 as 1.00 or less, and even further select (Li2O+Na2O+TiO2+WO3+Bi2O3+ZnO) / SiO2 as 0.50 or less. In some implementations, the value of (Li₂O+Na₂O+TiO₂+WO₃+Bi₂O₃+ZnO) / SiO₂ can be 0, greater than 0, 0.01, 0.03, 0.05, 0.07, 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, or 0.90. The values are 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, 1.35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.
[0041] RO (selected from one or more of MgO, CaO, SrO, and BaO) can improve the meltability of glass and adjust its optical constants. However, if its content is too high, the glass's resistance to crystallization decreases. Therefore, in this application, the RO content is 0-5%, optionally 0-3%, or optionally 0-1%. In some embodiments, it is further optional that RO is not present. In some embodiments, the RO content can be 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.
[0042] In some embodiments, controlling the ratio of the total content of P2O5, TiO2, RO, and Na2O (P2O5+TiO2+RO+Na2O) to the content of Nb2O5 (P2O5+TiO2+RO+Na2O) / Nb2O5 within the range of 0.30 to 0.90 can improve the glass's resistance to crystallization and acid resistance. Therefore, a ratio of (P2O5+TiO2+RO+Na2O) / Nb2O5 of 0.30 to 0.90 is optional, a ratio of (P2O5+TiO2+RO+Na2O) / Nb2O5 of 0.35 to 0.75 is optional, and a ratio of (P2O5+TiO2+RO+Na2O) / Nb2O5 of 0.35 to 0.60 is further optional. In some implementations, the value of (P2O5+TiO2+RO+Na2O) / Nb2O5 can be 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in implementations, any of the above ranges can be combined with any other range.
[0043] In some implementations, by controlling the ratio between the total content of Na2O, TiO2, WO3, Bi2O3, ZnO, and RO (Na2O+TiO2+WO3+Bi2O3+ZnO+RO) and the content of Al2O3 (Na2O+TiO2+WO3+Bi2O3+ZnO+RO) / Al2O3 below 1.50, it is possible to prevent an increase in the coefficient of thermal expansion of the glass, which is beneficial to obtaining a lower coefficient of thermal expansion of the glass. Therefore, it is possible to select (Na2O+TiO2+WO3+Bi2O3+ZnO+RO) / Al2O3 with a value of 1.50 or less, (Na2O+TiO2+WO3+Bi2O3+ZnO+RO) / Al2O3 with a value of 1.00 or less, further select (Na2O+TiO2+WO3+Bi2O3+ZnO+RO) / Al2O3 with a value of 0.50 or less, and even further select (Na2O+TiO2+WO3+Bi2O3+ZnO+RO) / Al2O3 with a value of 0.30 or less. In some implementations, the value of (Na2O+TiO2+WO3+Bi2O3+ZnO+RO) / Al2O3 can be 0, greater than 0, 0.01, 0.03, 0.05, 0.07, 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, 1.35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0044] In some embodiments, by controlling the value of (K2O-Na2O-TiO2-RO-WO3) / B2O3 within the range of 0.50 to 5.00, the Young's modulus of the glass can be increased while making it easier to obtain a suitable high-temperature viscosity. Therefore, (K2O-Na2O-TiO2-RO-WO3) / B2O3 can be selected as 0.50 to 5.00, (K2O-Na2O-TiO2-RO-WO3) / B2O3 can be selected as 0.80 to 3.00, (K2O-Na2O-TiO2-RO-WO3) / B2O3 can be selected as 1.00 to 2.50, and (K2O-Na2O-TiO2-RO-WO3) / B2O3 can be selected as 1.10 to 2.00.In some implementations, the value of (K2O-Na2O-TiO2-RO-WO3) / B2O3 can be 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, 1.35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, 2.03, 2.05, 2.07, 2.10, 2.13, 2.15, 2.17, 2 20, 2.23, 2.25, 2.27, 2.30, 2.33, 2.35, 2.37, 2.40, 2.43, 2.45, 2.47, 2.50, 2.53, 2.55, 2.57, 2.60, 2.63, 2.65, 2.67, 2.70, 2.73, 2.75, 2.77, 2.80, 2.83, 2.85, 2.87, 2.90, 2.93, 2.95, 2.97, 3.00, 3.05, 3.10, 3.15, 3.20, 3.25, 3. 30, 3.35, 3.40, 3.45, 3.50, 3.55, 3.60, 3.65, 3.70, 3.75, 3.80, 3.85, 3.90, 3.95, 4.00, 4.05, 4.10, 4.15, 4.20, 4.25, 4.30, 4.35, 4.40, 4.45, 4.50, 4.55, 4.60, 4.65, 4.70, 4.75, 4.80, 4.85, 4.90, 4.95, 5.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.
[0045] In this application, by using one or more components selected from Sb₂O₃, SnO₂, and CeO₂ as a clarifying agent containing 0-1%, the clarification effect of the glass can be improved, and the bubble content of the glass can be reduced. The content of the clarifying agent can be 0-0.5%, or 0-0.2%. In some embodiments, the content of the clarifying agent can be 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0046] <Components that should not be present>
[0047] In the glass of this application, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag, and Mo are contained in small amounts, either alone or in combination, the glass will be colored and absorb at specific wavelengths in the visible light region, thereby weakening the property of this application to improve visible light transmittance. Therefore, it is preferable to omit these oxides, especially for optical glass that requires transmittance in the visible light region.
[0048] Oxides of Th, Cd, Tl, Os, Be, and Se have been increasingly subject to controlled use in recent years due to their status as hazardous chemicals. Environmental protection measures are essential not only in glass manufacturing but also in processing and post-product disposal. Therefore, given the importance of environmental impact, it is preferable to eliminate these substances, except where their contamination is unavoidable. Consequently, the optical glass becomes virtually free of pollutants. Therefore, even without specific environmental countermeasures, the optical glass of this application can be manufactured, processed, and disposed of.
[0049] To achieve environmental friendliness, the optical glass in this application may be free of As2O3 and PbO.
[0050] The terms "not containing", "0%", and "0" used herein mean that the compound, molecule, or element was not intentionally added to the optical glass of this application as a raw material; however, as raw materials and / or equipment for producing optical glass, there may be certain impurities or components that are not intentionally added, which may be present in small or trace amounts (less than 0.01%) in the final optical glass, and such situations are also within the scope of protection of this patent application.
[0051] The performance of the high-dispersion optical glass of this application will now be described.
[0052] <Refractive Index and Abbe Number>
[0053] The refractive index (n) of optical glass d ) and Abbe number (ν d Tested according to the method specified in the national standard GB / T 7962.1—2010.
[0054] In some embodiments, the refractive index (n) of the high-dispersion optical glass of this application is... d The lower limit for (n) is 1.725, with an optional lower limit of 1.730 and an optional lower limit of 1.735. In some embodiments, the refractive index (n) of the optical glass of this application is... d The upper limit for (n) is 1.780, with optional upper limits of 1.770 and 1.760. In some implementations, the refractive index (n) is... d The range can be 1.725, 1.727, 1.730, 1.733, 1.735, 1.737, 1.740, 1.743, 1.745, 1.747, 1.750, 1.753, 1.755, 1.757, 1.760, 1.763, 1.765, 1.767, 1.770, 1.773, 1.775, 1.777, 1.780, etc., as well as all ranges and subranges between the above values.
[0055] In some embodiments, the Abbe number (ν) of the high-dispersion optical glass of this application d The lower limit is 22.0, with optional lower limits of 23.0 and 24.0. In some embodiments, the Abbe number (ν) of the optical glass of this application... d The upper limit for the Abbe number is 28.5, with an optional upper limit of 28.0 and an optional upper limit of 27.0. In some implementations, the Abbe number (ν) d The range can be 23.0, 23.3, 23.5, 23.7, 24.0, 24.3, 24.5, 24.7, 25.0, 25.3, 25.5, 25.7, 26.0, 26.3, 26.5, 26.7, 27.0, 27.3, 27.5, 27.7, 28.0, 28.3, 28.5, etc., as well as all ranges and subranges between the above values.
[0056] <Coefficient of thermal expansion>
[0057] The coefficient of thermal expansion of optical glass (α) 100℃ / 300℃ Data were tested at 100–300℃ according to the method specified in the national standard GB / T7962.16—2010.
[0058] In some embodiments, the coefficient of thermal expansion (α) of the high-dispersion optical glass of this application is... 100℃ / 300℃ ) is 95×10 -7For values below / K, 90×10 can be selected. -7 For values below / K, 85×10 can be selected. -7 Below / K, a further option is 80×10 -7 / K or below. In some embodiments, the coefficient of thermal expansion (α) is... 100℃ / 300℃ ) can be 95×10 -7 / K、94×10 -7 / K、93×10 -7 / K、92×10 -7 / K、91×10 -7 / K、90×10 -7 / K、89×10 -7 / K、88×10 -7 / K、87×10 -7 / K、86×10 -7 / K、85×10 -7 / K、84×10 -7 / K、83×10 -7 / K、82×10 -7 / K、81×10 -7 / K、80×10 -7 / K、79×10 -7 / K、78×10 -7 / K、77×10 -7 / K、76×10 -7 / K、75×10 -7 / K、74×10 -7 / K、73×10 -7 / K、72×10 -7 / K、71×10 -7 / K, etc., and all ranges and subranges between the above values.
[0059] <Stability under water resistance>
[0060] Water resistance stability of optical glass (D) W (Powder method) Tested according to the method specified in the national standard GB / T 17129. In this application, the stability of water resistance may be referred to as water resistance.
[0061] In some embodiments, the water resistance stability (D) of the high-dispersion optical glass of this application is... W If there are two or more categories, one category can be selected.
[0062] <Stability under acid conditions>
[0063] Acid resistance stability of optical glass (D) A(Powder method) Tested according to the method specified in the national standard GB / T 17129. In this application, the acid resistance stability can be simply referred to as acid resistance.
[0064] In some embodiments, the acid resistance stability (D) of the high-dispersion optical glass of this application is... A If there are two or more categories, one category can be selected.
[0065] <Density>
[0066] The density (ρ) of optical glass is tested according to the method specified in the national standard GB / T7962.20—2010.
[0067] In some embodiments, the density (ρ) of the high-dispersion optical glass of this application is 3.40 g / cm³. 3 The following can be selected as 3.30g / cm 3 The following can be selected as 3.20 g / cm³. 3 Below. In some embodiments, the density (ρ) can be 3.40 g / cm³. 3 3.39 g / cm 3 3.38g / cm 3 3.37 g / cm 3 3.36 g / cm 3 3.35g / cm 3 3.34 g / cm 3 3.33 g / cm 3 3.32g / cm 3 3.31 g / cm 3 3.30g / cm 3 3.29 g / cm 3 3.28g / cm 3 3.27 g / cm 3 3.26 g / cm 3 3.25g / cm 3 3.24 g / cm 3 3.23 g / cm 3 3.22g / cm 3 3.21 g / cm 3 3.20g / cm 3 3.19 g / cm 3 3.18 g / cm 3 3.17g / cm 3 3.16 g / cm 3 3.15g / cm 3 3.14 g / cm 3 3.13 g / cm 33.12 g / cm 3 3.11 g / cm 3 3.10 g / cm 3 And so on, as well as all ranges and subranges between the above values.
[0068] <Transition Temperature>
[0069] Transition temperature of optical glass (T) g Test according to the method specified in the national standard GB / T7962.16—2010.
[0070] If the transition temperature of optical glass is too high, it is not conducive to the manufacture of glass preforms and optical components through precision molding; if the transition temperature of optical glass is too low, it is not conducive to the application of optical glass in high-temperature environments. In some embodiments, the transition temperature (T0) of the high-dispersion optical glass of this application is... g The transition temperature (T) is 580℃~650℃, optionally 590℃~640℃, or optionally 600℃~620℃. In some embodiments, the transition temperature (T) is... g The values can be 580℃, 583℃, 585℃, 587℃, 590℃, 593℃, 595℃, 597℃, 600℃, 603℃, 605℃, 607℃, 610℃, 613℃, 615℃, 617℃, 620℃, 623℃, 625℃, 627℃, 630℃, 633℃, 635℃, 637℃, 640℃, 643℃, 645℃, 647℃, 650℃, etc., as well as all ranges and subranges between the above values.
[0071] <shading>
[0072] The short-wavelength transmission spectral characteristics of the glass in this application are expressed using colorimetry (λ). 80 ) represents. λ 80 This refers to the wavelength corresponding to a glass transmittance of 80%. λ 80 The measurement was performed using a glass with a thickness of 10 ± 0.1 mm and two optically polished, parallel planes. The spectral transmittance was measured in the wavelength range from 280 nm to 700 nm, and wavelengths exhibiting 80% transmittance were recorded. Spectroscopic transmittance, or transmittance, is the value of transmittance when an intensity I is incident perpendicularly onto the aforementioned surface of the glass. in Light passes through the glass and exits from a plane with an intensity of I. out In the case of light, through I out / I in The quantity represented, and also includes the transmittance, which accounts for the surface reflection loss on the aforementioned surfaces of the glass. In optical glass, λ 80 A smaller value means that the glass itself has less coloration and higher light transmittance.
[0073] In some embodiments, the chromaticity (λ) of the high-dispersion optical glass of this application 80 The chromaticity (λ) of the optical glass is below 440nm, optionally below 430nm, or optionally below 425nm. In some embodiments, the chromaticity (λ) of the optical glass... 80 The range can be 410nm, 411nm, 412nm, 413nm, 414nm, 415nm, 416nm, 417nm, 418nm, 419nm, 420nm, 421nm, 422nm, 423nm, 424nm, 425nm, 426nm, 427nm, 428nm, 429nm, 430nm, 431nm, 432nm, 433nm, 434nm, 435nm, 436nm, 437nm, 438nm, 439nm, 440nm, etc., as well as all ranges and subranges between the above values.
[0074] <Upper limit temperature for crystallization>
[0075] The upper limit temperature for crystallization of optical glass was determined using the gradient furnace method. Glass samples measuring 180mm × 10mm × 10mm were prepared, polished on the sides, and placed in a furnace with a temperature gradient (10℃ / cm) and a maximum temperature zone of 1200℃ for 4 hours. After being removed and allowed to cool naturally to room temperature, the crystallization was observed under a microscope. The highest temperature at which crystals appeared was defined as the upper limit temperature for crystallization. A lower upper limit temperature indicates better resistance to crystallization.
[0076] In some embodiments, the upper limit temperature for crystallization of the high-dispersion optical glass of this application is below 1070°C, optionally below 1050°C, or optionally below 1020°C. In some embodiments, the upper limit temperature for crystallization of the optical glass is 970°C, 980°C, 990°C, 1000°C, 1010°C, 1020°C, 1030°C, 1040°C, 1050°C, 1060°C, 1070°C, etc., as well as all ranges and sub-ranges between the above values.
[0077] Young's Modulus
[0078] Young's modulus (E) is obtained by ultrasonic testing of its longitudinal and transverse wave velocities, and then calculated using the following formula.
[0079]
[0080] G=V S 2 ρ
[0081] In the formula: E is Young's modulus, Pa;
[0082] G is the shear modulus, Pa;
[0083] V T The transverse wave velocity is in m / s;
[0084] V S The longitudinal wave velocity is given in m / s.
[0085] ρ is the density of glass, in g / cm³ 3 .
[0086] In some embodiments, the Young's modulus (E) of the high-dispersion optical glass of this application is 6800 × 10⁻⁶. 7 For pressures above Pa, 7000×10⁻⁶ can be selected. 7 For pressures above 10 Pa, 7500×10 Pa can be selected. 7 Pa or higher. In some embodiments, the Young's modulus (E) of the optical glass can be 6800 × 10⁻⁶. 7 Pa, 6850×10 7 Pa, 6900 × 10 7 Pa, 6950×10 7 Pa, 7000×10 7 Pa, 7050×10 7 Pa, 7100×10 7 Pa, 7150×10 7 Pa, 7200×10 7 Pa, 7250×10 7 Pa, 7300 × 10 7 Pa, 7350×10 7 Pa, 7400×10 7 Pa, 7450×10 7 Pa, 7500×10 7 Pa, 7550×10 7 Pa, 7600×10 7 Pa, 7650×10 7 Pa, 7700×10 7 Pa, 7750×10 7 Pa, 7800×10 7 Pa, 7850×10 7 Pa, etc., and all ranges and subranges between the above values.
[0087] Knoop Hardness
[0088] Knoop hardness (H) of optical glass K The test was conducted according to the test method specified in the national standard GB / T7962.18-2010. In this application, Knoop hardness may be referred to simply as hardness.
[0089] In some embodiments, the Knoop hardness (H) of the high-dispersion optical glass of this application is... K ) is 400×10 7 For pressures above 410 × 10 Pa, 410 × 10 Pa can be selected. 7 For pressures above 4, 420×10 can be selected. 7 Pa or higher. In some embodiments, the Knoop hardness (H) is... K (can be 400×10) 7 Pa, 405×10 7 Pa, 410×10 7 Pa, 415×10 7 Pa, 420×10 7 Pa, 425×10 7 Pa, 430×10 7 Pa, 435×10 7 Pa, 440×10 7 Pa, etc., and all ranges and subranges between the above values.
[0090] Viscosity
[0091] The viscosity of optical glass is tested using the following method: a THETA Rheotronic II high-temperature viscometer is used with a rotational method. The unit of measurement is dPas (poise). The lower the value, the lower the viscosity. Optical glass needs to have a suitable high-temperature viscosity to prevent streaks and / or crystallization during the glass forming process.
[0092] In some embodiments, the viscosity of the high-dispersion optical glass of this application at 1000°C is 3.0 dPaS to 50.0 dPaS, optionally 5.0 dPaS to 30.0 dPaS, optionally 8.0 dPaS to 20.0 dPaS. In some embodiments, the viscosity of the optical glass at 1000°C is 3.0 dPaS, 3.5 dPaS, 4.0 dPaS, 4.5 dPaS, 5.0 dPaS, 5.5 dPaS, 6.0 dPaS, 6.5 dPaS, 7.0 dPaS, 7.5 dPaS, 8.0 dPaS, 8.5 dPaS, 9.0 dPaS, 9.5 dPaS, 10.0 dPaS, 10.5 dPaS, 11.0 dPaS, 11.5 dPaS, or 12.0 dPaS. PaS, 12.5dPaS, 13.0dPaS, 13.5dPaS, 14.0dPaS, 14.5dPaS, 15.0dPaS, 15.5dPaS, 16.0dPaS, 16.5dPaS, 17. 0dPaS, 17.5dPaS, 18.0dPaS, 18.5dPaS, 19.0dPaS, 19.5dPaS, 20.0dPaS, 20.5dPaS, 21.0dPaS, 21.5dPaS, 2 2.0dPaS, 22.5dPaS, 23.0dPaS, 23.5dPaS, 24.0dPaS, 24.5dPaS, 25.0dPaS, 25.5dPaS, 26.0dPaS, 26.5dPa S, 27.0dPaS, 27.5dPaS, 28.0dPaS, 28.5dPaS, 29.0dPaS, 29.5dPaS, 30.0dPaS, 31.0dPaS, 32.0dPaS, 33.0d PaS, 34.0 dPaS, 35.0 dPaS, 36.0 dPaS, 37.0 dPaS, 38.0 dPaS, 39.0 dPaS, 40.0 dPaS, 41.0 dPaS, 42.0 dPaS, 43.0 dPaS, 44.0 dPaS, 45.0 dPaS, 46.0 dPaS, 47.0 dPaS, 48.0 dPaS, 49.0 dPaS, 50.0 dPaS, etc., as well as all ranges and subranges between the above values.
[0093] [Manufacturing methods for optical glass]
[0094] The manufacturing method of the optical glass in this application is as follows: The glass of this application is produced using conventional raw materials and processes, including but not limited to using oxides, hydroxides, complex salts (such as carbonates, nitrates, sulfates, phosphates, metaphosphates, etc.), boric acid, etc. as raw materials. After the raw materials are prepared according to conventional methods, the prepared furnace charge is put into a melting furnace (such as a platinum crucible, platinum alloy crucible, quartz crucible, etc.) at 1100-1300℃ for melting. After clarification and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained. This molten glass is then cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods, and process parameters according to actual needs.
[0095] [Glass preforms and optical components]
[0096] Glass preforms can be manufactured from the produced optical glass using methods such as direct drop forming, grinding, or hot pressing. Specifically, glass preforms can be manufactured by directly and precisely drop-forming molten optical glass into precision glass preforms, or by machining such as grinding and polishing, or by hot pressing a preform made from optical glass for compression molding followed by grinding. It should be noted that the methods for preparing glass preforms are not limited to the methods described above.
[0097] As described above, the high dispersion optical glass of this application is useful for various optical components and optical designs. In particular, the optical glass of this application can be used to form a preform, which can be used for hot pressing, precision stamping, etc., to manufacture optical components such as lenses and prisms.
[0098] Both the glass preform and the optical element in this application are formed from the high-dispersion optical glass described above. The glass preform of this application possesses the excellent properties of optical glass; the optical element of this application possesses the excellent properties of optical glass, and can provide various optical elements such as lenses and prisms with high optical value.
[0099] Examples of lenses include concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, plano-concave lenses, and so on, where the lens surface is spherical or aspherical.
[0100] [Device]
[0101] The high-dispersion optical glass and optical elements made of high-dispersion optical glass described in this application can be used to manufacture various devices (including instruments, equipment, etc.), such as imaging equipment, sensors, microscopes, medical technology, digital projection, communication, optical communication technology / information transmission, optics / lighting in the automotive field, photolithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices including such circuits and chips, or for use in the automotive field, and in the field of surveillance and security imaging equipment and instruments.
[0102] Example
[0103] <Examples of High Dispersion Optical Glass>
[0104] To further illustrate and explain the technical solution of this application, the following non-limiting embodiments are provided.
[0105] In this embodiment, optical glass with the compositions shown in Tables 1-1 to 3-1 was obtained using the optical glass manufacturing method described above. Furthermore, the properties of each glass were measured using the testing method described in this application, and the measurement results are shown in Tables 1-2 to 3-2.
[0106] Table 1-1.
[0107]
[0108] Table 1-2.
[0109]
[0110] Table 2-1.
[0111]
[0112] Table 2-2.
[0113]
[0114] Table 3-1.
[0115]
[0116] Table 3-2.
[0117]
[0118] <Example of Glass Prefabricated Components>
[0119] The glass obtained from the high dispersion optical glass examples 1# to 15# is used to manufacture glass preforms of various lenses and prisms, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses, by means of grinding, hot pressing, precision stamping, or other molding methods.
[0120] <Optical Component Examples>
[0121] Annealing these preforms obtained from the above glass preform examples reduces internal stress in the glass while fine-tuning the refractive index, so that optical properties such as the refractive index reach the desired values.
[0122] Next, the prefabricated parts are ground and polished to produce various lenses and prisms, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. Anti-reflective coatings can also be applied to the surface of the resulting optical elements.
[0123] <Device Embodiment>
[0124] The optical elements obtained from the above-described optical element embodiments can be used, through optical design, to form optical components or optical assemblies by using one or more optical elements. These components can be used in, for example, imaging devices, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, lithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices that include such circuits and chips.
[0125] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0126] The embodiments described above are merely illustrative of several implementation methods of this application, intended to facilitate a detailed understanding of the technical solutions of this application, but should not be construed as limiting the scope of protection of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the scope of protection of this application. It should be understood that technical solutions obtained by those skilled in the art based on the technical solutions provided in this application through logical analysis, reasoning, or limited experimentation are all within the scope of protection of the appended claims. Therefore, the scope of protection of this patent application should be determined by the content of the appended claims, and the specification can be used to interpret the content of the claims.
Claims
1. A high-dispersion optical glass, characterized in that, Its composition, expressed as a weight percentage, contains: P2O5: 16%–29%; Nb2O5: 41%–53%; SiO2: greater than or equal to 1% but less than 10%; B2O3: 3%–15%; K2O: 8.5%–20%; Al2O3: greater than 0% but less than or equal to 8%, of which Nb2O5 / (SiO2+Al2O3) is 3.00–10.
00.
2. The high-dispersion optical glass according to claim 1, characterized in that, Its components, expressed as a weight percentage, also contain: Na2O: 0–5%; and / or Li2O: 0–5%; and / or ZrO2: 0–5%; and / or WO3: 0–5%; and / or TiO2: 0–4%; and / or ZnO: 0–5%; and / or Ln2O3: 0–5%; and / or Bi2O3: 0–3%; and / or RO: 0–5%; and / or clarifying agent: 0–1%, wherein the RO is selected from one or more of MgO, CaO, SrO, and BaO, the Ln2O3 is selected from one or more of La2O3, Gd2O3, Y2O3, and Yb2O3, and the clarifying agent is selected from one or more of Sb2O3, SnO2, and CeO2.
3. A high-dispersion optical glass, characterized in that, The high-dispersion optical glass contains P2O5, Nb2O5, SiO2, B2O3, K2O, and Al2O3 as essential components, expressed as weight percentages. The ratio of Nb2O5 / (SiO2+Al2O3) is 3.00–10.
00. The Abbe number of the high-dispersion optical glass is 22.0–28.5, and its density is 3.40 g / cm³. 3 The coefficient of thermal expansion α is as follows. 100℃ / 300℃ 95×10 -7 / K or below.
4. The high-dispersion optical glass according to claim 3, characterized in that, Its composition, expressed as a weight percentage, contains: P2O5: 16%–29%; and / or Nb2O5: 41%–53%; and / or SiO2: greater than or equal to 1% but less than 10%; and / or B2O3: 3%–15%; and / or K2O: 8.5%–20%; and / or Al2O3: greater than 0% but less than or equal to 8%; and / or Na2O: 0–5%; and / or Li2O: 0–5%; and / or ZrO2: 0–5%; and / or WO3: 0–5%. ; and / or TiO2: 0-4%; and / or ZnO: 0-5%; and / or Ln2O3: 0-5%; and / or Bi2O3: 0-3%; and / or RO: 0-5%; and / or clarifying agent: 0-1%, wherein the RO is selected from one or more of MgO, CaO, SrO, and BaO, the Ln2O3 is selected from one or more of La2O3, Gd2O3, Y2O3, and Yb2O3, and the clarifying agent is selected from one or more of Sb2O3, SnO2, and CeO2.
5. The high-dispersion optical glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as weight percentages, wherein: Nb2O5 / (SiO2+Al2O3) is 3.50–9.00, optionally Nb2O5 / (SiO2+Al2O3) is 4.00–8.50, optionally Nb2O5 / (SiO2+Al2O3) is 5.00–7.50; and / or (K2O-Na2O-TiO2-RO-WO3) / B2O3 is 0.50–5.00, optionally (K2O-Na2O-TiO2-R The ratio of (K2O-Na2O-TiO2-RO-WO3) / B2O3 is 0.80–3.00, and optionally (K2O-Na2O-TiO2-RO-WO3) / B2O3 is 1.00–2.50, further optionally (K2O-Na2O-TiO2-RO-WO3) / B2O3 is 1.10–2.00; and / or (Li2O+Na2O+TiO2+WO3+Bi2O3+ZnO) / SiO2 is below 2.00, optionally (Li2O+Na2O+TiO3) / B2O3 is 1.10–2.
00. The ratio of (O2+WO3+Bi2O3+ZnO) / SiO2 is 1.50 or less, optionally (Li2O+Na2O+TiO2+WO3+Bi2O3+ZnO) / SiO2 is 1.00 or less, and further optionally (Li2O+Na2O+TiO2+WO3+Bi2O3+ZnO) / SiO2 is 0.50 or less; and / or (Na2O+TiO2+WO3+Bi2O3+ZnO+RO) / Al2O3 is 1.50 or less. The ratio of (Na2O+TiO2+WO3+Bi2O3+ZnO+RO) / Al2O3 can be 1.00 or less, or 0.50 or less, or even 0.30 or less, wherein RO is selected from one or more of MgO, CaO, SrO, and BaO.
6. The high-dispersion optical glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as weight percentages, wherein: Al2O3 / SiO2 is 0.10–3.00, optionally Al2O3 / SiO2 is 0.20–2.00, optionally Al2O3 / SiO2 is 0.30–1.50, and further optionally Al2O3 / SiO2 is 0.40–0.80; and / or (B2O3+K2O) / P2O5 is 0.80–2.00, optionally (B2O3+K2O) / P2O5 is 0.90–1.70, optionally (B2O3+K2O) / P2O5 is 1.00–1.40; and / or K2O / (P2O5+TiO2) The K2O / (P2O5+TiO2) ratio is 0.35–1.10, and the K2O / (P2O5+TiO2) ratio is 0.40–0.95, or the K2O / (P2O5+TiO2) ratio is 0.50–0.80; and / or the (P2O5+TiO2+RO+Na2O) / Nb2O5 ratio is 0.30–0.90, or the (P2O5+TiO2+RO+Na2O) / Nb2O5 ratio is 0.35–0.75, or the (P2O5+TiO2+RO+Na2O) / Nb2O5 ratio is 0.35–0.60, wherein the RO is selected from one or more of MgO, CaO, SrO, and BaO.
7. The high-dispersion optical glass according to any one of claims 1 to 4, characterized in that, Its components, expressed as a weight percentage, contain: P2O5: 18%–26%, optional P2O5: greater than 20% but less than or equal to 24%; and / or Nb2O5: 43%–51%, optional Nb2O5: 45.5%–50%; and / or SiO2: 2%–9%, optional SiO2: 3%–8%; and / or B2O3: 5%–13%, optional B2O3: 7%–11%; and / or K2O: 10.5%–18%. Optional K2O: 12%–16%; and / or Al2O3: 0.5%–6%, with optional Al2O3: 1%–5%; and / or Na2O: 0–3%, with optional Na2O: 0–1%, or optional Na2O-free; and / or Li2O: 0–3%, with optional Li2O: 0–1%, or optional Li2O-free; and / or ZrO2: 0–3%, with optional ZrO2: 0–1%, or optional ZrO2-free; and / or WO3: 0%–1 ... ~3%, optional WO3: 0~1%, optional not containing WO3; and / or TiO2: 0~2%, optional TiO2: 0~1%, optional not containing TiO2; and / or ZnO: 0~3%, optional ZnO: 0~1%, optional not containing ZnO; and / or Ln2O3: 0~3%, optional Ln2O3: 0~1%, optional not containing Ln2O3; and / or Bi2O3: 0~2%, optional Bi2O3: 0~1%, optional It does not contain Bi2O3; and / or RO: 0-3%, optional RO: 0-1%, optional not containing RO; and / or clarifying agent: 0-0.5%, optional clarifying agent: 0-0.2%, wherein the RO is selected from one or more of MgO, CaO, SrO, and BaO, Ln2O3 is selected from one or more of La2O3, Gd2O3, Y2O3, and Yb2O3, and the clarifying agent is selected from one or more of Sb2O3, SnO2, and CeO2.
8. The high-dispersion optical glass according to any one of claims 1 to 4, characterized in that, The high-dispersion optical glass has a refractive index of 1.725–1.780, optionally 1.730–1.770, optionally 1.735–1.760; and / or an Abbe number of 22.0–28.5, optionally 23.0–28.0, optionally 24.0–27.0; and / or a coefficient of thermal expansion α. 100℃ / 300℃ 95×10 -7 For values below / K, 90×10 can be selected. -7 For values below / K, 85×10 can be selected. -7 Below / K, a further option is 80×10 -7 / K or below; and / or density of 3.40 g / cm³ 3 The following can be selected as 3.30g / cm 3 The following can be selected as 3.20 g / cm³. 3 The following; and / or Young's modulus is 6800×10 7 For pressures above 10 Pa, 7000×10 Pa can be selected. 7 For pressures above 10 Pa, 7500×10 Pa can be selected. 7 Pa or higher; and / or water resistance stability of Class 2 or higher, Class 1 optional; and / or acid resistance stability of Class 2 or higher, Class 1 optional; and / or transition temperature of 580℃~650℃, 590℃~640℃ optional, 600℃~620℃ optional; and / or crystallization upper limit temperature of 1070℃ or lower, 1050℃ or lower optional, 1020℃ optional; and / or Knoop hardness of 400×10⁻⁶. 7 For pressures above 410 × 10 Pa, 410 × 10 Pa can be selected. 7 For Pa above, 420×10 can be selected. 7 Pa or above; and / or chromaticity λ 80 The wavelength is below 440 nm, optionally below 430 nm or 425 nm; and / or the viscosity at 1000℃ is 3.0 dPaS to 50.0 dPaS, optionally 5.0 dPaS to 30.0 dPaS or 8.0 dPaS to 20.0 dPaS.
9. A glass precast component, characterized in that, It is made of the high dispersion optical glass described in any one of claims 1 to 8.
10. An optical element, characterized in that, It is made of the high dispersion optical glass as described in any one of claims 1 to 8, or of the glass preform as described in claim 9.
11. An apparatus, characterized in that, It contains the high dispersion optical glass according to any one of claims 1 to 8, and / or contains the optical element according to claim 10.
Citation Information
Patent Citations
Optical glass, glass preform, optical element and optical instrument
CN119930146A